Pendampingan Pelaksanaan Disiplin Bahasa dengan Pendekatan Logic Consequence Di Pondok Modern - Syafii, Muhammad Lukman; Sugianto, Alip; Cendriono, Nanang (Universitas Nusantara PGRI Kediri, 2019)
This Science and Technology Activities for Communities is to approve sanctions applied in upholding the discipline of language in modern boarding school which fall into the category of punishment or logical consequences, which support can instill a high awareness in students to use language only to be able to enforce it as requested, but more because of the awareness of the importance of this language in the learning process. The method applied in this PKM activity was published in several stages, namely: discussing and enforcing debates on language discipline, socialization programs to modern cottage leaders, seminars on Punishment VS Logic Consequences, followed by workshops on language safety agreements with logical consequences, Preparing relevant punishment for students who commit an offense. In the end, from the implementation of the PKM program, it is hoped that the modern boarding school will no longer use punishment consisting of punishment in the enforcement of language discipline but instead uses logical agreement, so as to increase the awareness and interest of students in learning foreign languages.